2019
DOI: 10.1038/s41598-019-38882-3
|View full text |Cite
|
Sign up to set email alerts
|

Low-cost Fabrication of Tunable Band Gap Composite Indium and Gallium Nitrides

Abstract: III-nitride materials have been linked with a vast number of exciting applications from power electronics to solar cells. Herein, polycrystalline InN, GaN and systematically controlled InxGa1−xN composite thin films are fabricated on FTO glass by a facile, low-cost and scalable aerosol assisted chemical vapor deposition technique. Variation of the indium content in the composite films leads to a dramatic shift in the optical absorbance properties, which correlates with the band edges shifting between those of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 77 publications
1
19
0
Order By: Relevance
“…Ga 1– x In x N is a promising material with relatively higher robustness to resist corrosion in acidic or alkaline electrolytes. Moreover, one can modulate the bandgap (0.65–3.4 eV) by controlling the indium content. The band edge positions of Ga 1– x In x N cover the oxidation and reduction potentials of the water. They are capable of conducting PEC reactions without external bias. , Some research groups have reported that high In-containing Ga 1– x In x N with a narrow bandgap potentially has a higher photocurrent in PEC applications. , Nevertheless, it is hard to grow both high-quality and thick Ga 1– x In x N films on substrates (e.g., gallium nitride (GaN) or sapphire) because of the large lattice mismatch between GaN and Ga 1– x In x N. Consequently, the performance of Ga 1– x In x N-based photoelectrodes is limited by severe bulk recombination, which arises from numerous trap states in Ga 1– x In x N films. In this study, n -GaN epitaxial films, which have superior material quality compared to Ga 1– x In x N films, were used to fabricate the photoelectrodes to conduct PEC experiments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ga 1– x In x N is a promising material with relatively higher robustness to resist corrosion in acidic or alkaline electrolytes. Moreover, one can modulate the bandgap (0.65–3.4 eV) by controlling the indium content. The band edge positions of Ga 1– x In x N cover the oxidation and reduction potentials of the water. They are capable of conducting PEC reactions without external bias. , Some research groups have reported that high In-containing Ga 1– x In x N with a narrow bandgap potentially has a higher photocurrent in PEC applications. , Nevertheless, it is hard to grow both high-quality and thick Ga 1– x In x N films on substrates (e.g., gallium nitride (GaN) or sapphire) because of the large lattice mismatch between GaN and Ga 1– x In x N. Consequently, the performance of Ga 1– x In x N-based photoelectrodes is limited by severe bulk recombination, which arises from numerous trap states in Ga 1– x In x N films. In this study, n -GaN epitaxial films, which have superior material quality compared to Ga 1– x In x N films, were used to fabricate the photoelectrodes to conduct PEC experiments.…”
Section: Introductionmentioning
confidence: 99%
“…They are capable of conducting PEC reactions without external bias. 12,13 Some research groups have reported that high In-containing Ga 1−x In x N with a narrow bandgap potentially has a higher photocurrent in PEC applications. 14,15 Nevertheless, it is hard to grow both highquality and thick Ga 1−x In x N films on substrates (e.g., gallium nitride (GaN) or sapphire) because of the large lattice mismatch between GaN and Ga 1−x In x N. Consequently, the performance of Ga 1−x In x N-based photoelectrodes is limited by severe bulk recombination, which arises from numerous trap states in Ga 1−x In x N films.…”
Section: ■ Introductionmentioning
confidence: 99%
“…9−11 In addition, it possesses an appropriate band position to propel the hydrogen evolution reaction and oxygen evolution reaction simultaneously. 12,13 Meanwhile, the bandgap of GaN-based semiconductors can be tailored by incorporating indium (In) into Ga 1−x In x N and thereby have a more efficient photoresponse to solar radiation. 14−18 Nevertheless, high-quality and sufficiently thick Ga 1−x In x N films are difficult to grow on substrates (e.g., GaN or sapphire).…”
Section: Introductionmentioning
confidence: 99%
“…PEC reactions conducted using n-gallium nitride (GaN) epitaxial films as working electrodes (WEs) have at least one advantage in that GaN is considerably resistant to acidic or alkaline electrolytes compared with Si and GaAs. In addition, it possesses an appropriate band position to propel the hydrogen evolution reaction and oxygen evolution reaction simultaneously. , Meanwhile, the bandgap of GaN-based semiconductors can be tailored by incorporating indium (In) into Ga 1– x In x N and thereby have a more efficient photoresponse to solar radiation. Nevertheless, high-quality and sufficiently thick Ga 1– x In x N films are difficult to grow on substrates (e.g., GaN or sapphire). Given the large lattice mismatch between GaN and Ga 1– x In x N, numerous structural defects, such as dislocations, are produced in the films during the epitaxial growth.…”
Section: Introductionmentioning
confidence: 99%
“…III-nitride-based photoelectrodes, specifically Ga x In 1– x N, are suitable for absorbing the entire solar spectrum by controlling the indium content. The band edges of Ga x In 1– x N can straddle the water redox potential that enables water splitting without applying an external bias. , However, the thickness limit of high-quality Ga x In 1– x N epitaxial layers grown on a gallium nitride (GaN)/sapphire substrate is only hundreds of nanometers because of the large lattice mismatch between Ga x In 1– x N and GaN, especially for high-indium-containing materials. Consequently, achieving Ga x In 1– x N absorption layers with a low band gap (<2.0 eV) and a large thickness is still a challenge .…”
Section: Introductionmentioning
confidence: 99%